Pathogenesis of Psoriasis vulgaris and Current Management and Therapeutic Strategies Including the Role of Emollients—A Review of the Current Literature - Małgorzata Katarzyna Kowalska; Sara Małgorzata Orłowska; Łukasz Bednarczyk; Joanna Elżbieta Majewska; Weronika Hudecka (Applied Sciences, 2025)
Psoriasis is a chronic inflammatory skin disease with a complex clinical picture that remains incurable and requires ongoing dermatological care. The purpose of this literature review is to identify the latest therapeutic strategies used to treat psoriasis, taking into account both the efficacy of modern approaches and their impact on patients’ quality of life. The cornerstone of psoriasis treatment remains regular skin care through the use of emollients, which support the effectiveness of other topical therapies used such as corticosteroids. In addition, the review presents current epidemiological data on the prevalence of psoriasis worldwide, with a focus on European countries and Poland. The article discusses innovative approaches in therapy, including targeted biologics, modern forms of topical therapy, and the role of emollients in comprehensive skin care, as well as various cosmetological treatments aimed at removing the excessively accumulated stratum corneum, and improving the degree of hydration of psoriatic skin. The review also included current expert recommendations and guidelines from scientific societies that guide the treatment and care of psoriatic skin. The results of the analyses underscore the need for targeted therapies and the importance of a holistic approach to patient care. As the collected data indicate, the possibilities for effective topical and systemic treatment of psoriasis are increasing all the time due to research into newer and newer active substances that are expected to improve the efficacy of treatment, the comfort of life for psoriasis patients and reduce the side effects of long-term therapy.